Literacy and illiteracy, its relational other : A key topic for collaboration between psychology and anthropology - Alber, Erdmute; Kölbl, Carlos (Ethos, 2025)
Collaborative work between anthropology and psychology on literacy and particularly on illiteracy helps to rethink general disciplinary backgrounds, concepts, and complex empirical phenomena in the field of (il)literacy. Since the formational period of the social sciences, the concept of literacy has been key to the self-understandings of anthropology and psychology. However, it was long neglected in empirical research. Nonetheless, implicit and explicit assumptions about the role, history, and distinctiveness of writing systems and their presence or absence in various societies were central to disciplinary understandings of societies, individuals, and humanity. To this day, literacy and especially its relational other—illiteracy—have not received the attention they deserve from either empirical or conceptual research. This article begins with their histories in anthropology and psychology and argues that illiteracy, in particular, has been neglected in their debates. It then offers a framework for literacizing and illiteracizing, conceptualizes both illiteracy and literacy as multiple and relational phenomena, and discusses methodologies and preliminary results from our collaborative research project on processes of literacizing and illiteracizing in urban literate environments in Benin and Bolivia. It concludes with a discussion of the potential of research on literacy and illiteracy as a model for transdisciplinary work, especially a more intensive collaboration between our disciplines.
Keywords: Benin; Bolivia; Illiteracy; Literacy; multiplicity; Relationality; transdisciplinarity